Construction of Masculinity The Little Rascals (1994) - Ani Mulyani (Passage, 2017)
Masculinity in film is constructed differently, mirroring its construction in the real life. The purpose of the study is to examine the construction of masculinity in The Little Rascals (1994) directed by Penelope Spheeris. Using qualitative method, the study employs theory of masculinity (Connell, 2005), film theory (Heintz Stracey, 2006), and theory of characterization (Boggs Petrie, 2008). The findings show that masculinity in the film is constructed through dialogues and shots. There are two prominent types of masculinity, hegemonic masculinity which is upheld by the main characters Spanky and his gang and complicit masculinity which is upheld by Alfalfa. However, both Spanky and Alfalfa move from one type of masculinity to another; thus strengthening the argument that masculinity construction in the film is fluid.Keywords: Masculinity, construction, hegemonic masculinity, complicit masculinityKeywords: Masculinity, construction, hegemonic masculinity, complicit masculinity